Penerapan Metode Certainty Factor untuk Mendiagnosa Penyakit THT - Kristian Siregar; Paska Marto Hasugian (JUKI : Jurnal Komputer dan Informatika, 2019)
Expert system is a system that seeks to adopt human knowledge into computers, so that computers can solve problems like experts do. ENT (ears, nose, and throat) are organs that are closely interconnected. Abnormalities in these organs are diagnosed and treated by a specialist doctor. One of the functions of these organs such as the ear. The ear is an organ for hearing and balance consisting of the outer ear, middle ear and inner ear. The function of the nose, the nose is the olfactory organ and the main way in and out of air, the nose also provides additional sound resonance and is a place for paranasal sinuses and tear ducts. While the function of the throat is a muscular duct where the food goes to the esophagus and where the air travels to the lungs. In this study, an expert system was built to detect and be equipped with a certainty value of the diagnosis. The certainty value is obtained using the Certainty Factor (CF) method.